COMPARISON OF POSTOPERATIVE MEAN OPIOIDS CONSUMPTION IN PATIENT GIVEN PREOPERATIVE GABAPENTIN AND PLACEBO UNDERGOING MAJOR LAPAROTOMIES FOR LOWER ABDOMEN AND PELVIS - Muhammad Javed; Khaleel Ahmad; Anser Ali Butter (Journal of University Medical & Dental College, 2017)
ABSTRACT: OBJECTIVE: The objective of the study was to compare postoperative mean opioids consumption in patient given preoperative gabapentin and placebo undergoing major explorative laparotomies for lower abdomen and pelvis. STUDY DESIGN: Randomized controlled trial PLACE AND DURATION WITH DATES: Department of Anesthesiology, Hameed Latif hospital, Lahore, affiliated with College of Physicians & Surgeons of Pakistan, from 29-09-2009 to 29-032010. METHODOLOGY: This was a randomized controlled trial included 150 patients undergoing major laparotomies who were divided in two equal groups. In group I, 75 patients received multivitamin tab. as placebo and in group II, 75 patients had Gabapentin. The two groups were compared for the consumption dose of opioids analgesia, postoperatively. T-test was applied for statistical difference. (p- Value < 0.05 was taken as significant. Data was collected on special designed proforma. RESULTS: The mean dose of tramadol consumed by the patients in group I was 553.47 + 118.93 and in group II was 446.67+ 128.65 milligrams. CONCLUSION: The preoperative administration of Gabapentin before major laparotomies is recommended to reduce the postoperative dose of opioids analgesia.